1999
DOI: 10.1063/1.124609
|View full text |Cite
|
Sign up to set email alerts
|

Homoepitaxial growth of GaN by metalorganic vapor phase epitaxy: A benchmark for GaN technology

Abstract: Carefully optimized low-pressure metalorganic vapor phase epitaxy is used for homoepitaxial growth on distinctively pretreated GaN bulk single crystal substrates. Thereby, outstanding structural and optical qualities of the material have been achieved, exhibiting photoluminescence linewidths for bound excitons as narrow as 95 μeV. These extremely sharp lines reveal fine structures, not reported for GaN. Additionally, all three free excitons as well as their excited states are visible in low-temperature photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 14 publications
1
19
0
2
Order By: Relevance
“…As observed by other groups [16][17][18], high-resolution PL studies confirmed the high-crystalline quality of our undoped and Si-doped GaN homoepitaxial layers [19]. In particular, the Si-doped homoepitaxial sample exhibits sharper excitonic PL (linewidthsp1 meV) compared to that reported previously for GaN grown on Al 2 O 3 with similar Si doping levels [20].…”
Section: Gan Homoepitaxial Layerssupporting
confidence: 67%
See 1 more Smart Citation
“…As observed by other groups [16][17][18], high-resolution PL studies confirmed the high-crystalline quality of our undoped and Si-doped GaN homoepitaxial layers [19]. In particular, the Si-doped homoepitaxial sample exhibits sharper excitonic PL (linewidthsp1 meV) compared to that reported previously for GaN grown on Al 2 O 3 with similar Si doping levels [20].…”
Section: Gan Homoepitaxial Layerssupporting
confidence: 67%
“…Though not nearly as sharp as the excitonic PL observed from undoped GaN homoepitaxial layers with linewidths of B0.1 meV [16][17][18][19], the bandedge emission from these free-standing (thick) HVPE GaN templates is characterized by linewidths less than 1 meV [14]. An example of a high-resolution PL spectrum obtained at 5 K that demonstrates the high crystallinity of this material is shown in the inset of Fig.…”
Section: Free-standing (Thick) Hvpe Ganmentioning
confidence: 99%
“…Meanwhile, it is generally accepted that at higher temperature and higher pumping intensity, stimulated emission is governed by EHP. To reveal intrinsic mechanisms responsible for stimulated emission in GaN, state-of-the-art quality homoepitaxial layers [8,9] can be used.…”
mentioning
confidence: 99%
“…The FWHM of the bound exciton lines less than 0.5 meV is observed for layers grown by both MOCVD (i.e. [17,18]) and MBE (i.e. [19,20]) on the Ga-polar surface of the GaN substrates.…”
Section: Gan Homoepitaxy On Gan Pressure Grown Substratesmentioning
confidence: 93%